PERAN GURU PAUD DALAM PENDAMPINGAN PERKEMBANGAN MOTORIK ANAK PENYANDANG DISABILITAS - Angrilya Jein Romantika; Erawati Dwi Putri Date; Frilfa Sima; Hawila Pabali; Heslinda Mora’ (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
Motor development is an important aspect in the growth and development of early childhood, including for children with disabilities who often experience obstacles in motor skills and body coordination. In the context of inclusive education, early childhood education teachers have a strategic role in providing appropriate guidance and stimulation to support children's motor development. This research is motivated by the importance of the role of teachers in helping children with disabilities achieve optimal motor development and the limited studies that specifically discuss this role in early childhood education. This study aims to describe and analyze the role of early childhood education teachers in assisting the motor development of children with disabilities. This study uses a qualitative approach with a descriptive research type. Data were obtained through literature studies by reviewing various books, scientific journals, laws and regulations, and other relevant sources related to the role of early childhood education teachers, early childhood motor development, children with disabilities, and inclusive education. The collected data were analyzed descriptively to gain a comprehensive understanding of the phenomenon studied. The results of the study indicate that early childhood education teachers have an important role as facilitators, guides, motivators, mediators, and companions in supporting the motor development of children with disabilities. Teachers play a key role in designing learning activities tailored to children's needs, providing ongoing motor stimulation, and creating an inclusive and supportive learning environment. The success of mentoring is influenced by teacher competence, child characteristics, family support, and the availability of adequate facilities and infrastructure. Based on the research findings, it can be concluded that the role of early childhood education (PAUD) teachers is crucial for the success of mentoring the motor development of children with disabilities. Therefore, it is necessary to improve teacher competence, strengthen collaboration with parents, and develop more optimal inclusive education services. Further research is recommended to conduct field studies to gain a more in-depth understanding of the practice of mentoring the motor development of children with disabilities.